Transgenic Overproduction of Omega-3 Polyunsaturated Fatty Acids Provides Neuroprotection and Enhances Endogenous Neurogenesis After Stroke - Hu, X.; Zhang, F.; K. Leak, R.; Zhang, W.; Iwai, M.; A. Stetler, R.; Dai, Y.; Zhao, A.; Gao, Y.; Chen, J. (Current Molecular Medicine, 2013)
Strokes are devastating as there are no current therapies to prevent the long term neurological deficits that they cause. Soon after ischemic stroke, there is proliferation and differentiation of neural stem/progenitor cells as an important mechanism for neuronal restoration. However, endogenous neurogenesis by itself is insufficient for effective brain repair after stroke as most newborn neurons do not survive. One fascinating strategy for stroke treatment would thus be maintaining the survival and/or promoting the differentiation of endogenous neural stem/progenitor cells. Using transgenic (Tg) mice over-expressing the C. elegans fat-1 gene encoding an enzyme that converts endogenous omega-6 to omega-3 polyunsaturated fatty acids (n-3 PUFAs), we showed that fat-1 Tg mice with chronically elevated brain levels of n-3 PUFAs exhibited less brain damage and significantly improved long-term neurological performance compared to wild type littermates. Importantly, post-stroke neurogenesis occurred more robustly in fat-1 Tg mice after focal ischemia. This was manifested by enhanced neural stem cell proliferation/differentiation and increased migration of neuroblasts to the ischemic sites where neuroblasts matured into resident neurons. Moreover, these neurogenic effects were accompanied by significantly increased oligodendrogenesis. Our results suggest that n-3 PUFA supplementation is a potential neurogenic and oligodendrogenic treatment to naturally improve post-stroke brain repair and long-term functional recovery.
Keywords: Oligodendrogenesis